Co-precipitation assisted preparation of Ag2O, CuO and Ag2O/CuO nanocomposite: Characterization and improved solar irradiated degradation of colored and colourless organic effluents. Issue 13 (1st July 2022) - Warsi, Al-Zoha; Hussien, Omima K.; Iftikhar, Ayesha; Aziz, Fatima; Alhashmialameer, Dalal; Mahmoud, Samy F.; Warsi, Muhammad Farooq; Saleh, Dalia I.
Abstract: The photocatalytic degradation ability of Ag2 O/CuO nanocomposite was investigated to remove colored and colorless dyes under solar light irradiation. The pristine metal oxides (Ag2 O and CuO) were prepared using the co-precipitation method. The Ag2 O/CuO nanocomposite was prepared by an ultra-sonication route. The X-Rays Diffraction (XRD) were recorded to obtain phase analysis and crystallite size determination. The crystallite size of Ag2 O and CuO was 17.55 nm and 17.42 nm respectively. The spectral data obtained from Fourier Transform Infrared Spectroscopy (FTIR) analysis were also in agreement with the literature that ensured the formation of metal oxides. The Tauc plots were drawn to calculate the band gap energies, demonstrating that the nanocomposite formation caused several changes in electronic structure suitable for photocatalysis under solar light. The value of bandgap energy of nanocomposite was 1.51 eV which is less than pristine metal oxides such as CuO (2.77 eV) and Ag2 O (1.61 eV). The percentage degradation of methylene blue, rhodamine B and benzoic acid using nanocomposite was 97.5%, 90.5% and 95%, which is far better than that of pure metal oxides. The results demonstrated that the as-synthesized nanocomposite has tremendous potential to degrade the toxic pollutants in minimum time duration. Graphical abstract: Image 1